Pengaruh Harga dan Citra Merek terhadap Minat Beli Masyarakat pada Hiour Parfume di Kelurahan Taman Pinang Sidoarjo - Virda Kurnia Sari; Fonni Yeisa Putri; Yustira Dwi Julianti (PUTRA JAWA PUBLISHER, 2023)
This research was conducted by the authors to fulfill a campus program, namely the Student Entrepreneurship Program or what is often called PKM. The research was conducted in Taman Pinang Sidoarjo. With regard to this research, the object of this research is people's buying interest which is influenced by the price and brand of Hiour perfume. The purpose of this research is to find out the influence of price and brand image on the buying interest of the people in Taman Pinang Sidoarjo. The data collection method that the writer needs for this writing material is observation by directly observing the object under study and literature study. While the data analysis used is quantitative analysis.